Investigation of surface roughness in turning AISI 1020 steel using minimum quantity lubrication (MQL) with recycled cooking oil - Rismanto, Muhammad; Sirajuddin, Awal Syahrani; Hair, Jumaddil; Hidayat, Hidayat; Yandi, Yandi; Rozy, Fachrul (Jurnal Polimesin, 2025)
This study investigates the influence of the Minimum Quantity Lubrication (MQL) technique and spindle speed on the surface roughness of AISI 1020 steel during turning operations. recycled cooking oil was utilized as an environmentally friendly MQL lubricant, offering potential as a substitute for conventional mineral oils. In this experiment, two independent variables were considered: the lubrication condition (MQL and dry cutting) and spindle speed, which was tested at three levels (630 rpm, 800 rpm, and 1000 rpm). The dependent variable was surface roughness. MQL was selected due to its ability to enhance cooling and lubrication efficiency while minimizing environmental impacts. Experimental results indicated that at a spindle speed of 1000 rpm, surface roughness achieved 2,221 µm with MQL, compared to 2,824 µm without MQL. These findings highlight that recycled cooking oil-based MQL significantly improves the surface finish and demonstrate that the proper combination of lubrication parameters and spindle speed enhances machining quality. Moreover, this research supports sustainable manufacturing by promoting the use of Recycled Cooking Oil as a green lubricant alternative.